PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL DALAM PROSPEKTUS TERHADAP UNDERPRICING SAHAM (Studi pada Perusahaan yang Melakukan Initial Public Offering di BEI Periode 2007-2012) - Kurniawan, Warih Widya; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the effect of intellectual capital disclosure in prospectus on underpricing level at initial public offering. Independent variable used in this study is intellectual capital disclosure. This study also used control variables, e.g underwriter’s reputation, gross proceeds, auditor’s reputation, financial leverage, company’s age, and company’s size.Samples of this study were IPO companies in Indonesia Stock Exchange, for the observation period of 2007 until 2012. Samples were taken by purposive sampling method and resulted in 91 companies as the samples. This study used linear regression for analysing data.The result showed that intellectual capital disclosure affect underpricing significantly. Auditor’s reputation, financial leverage, company’s age. And company’s size as the control variables have negative and significant effect on underpricing. However, underwriter’s reputation show negative effect on underpricing, and not significant. In the other side, gross proceeds impact underpricing positively and not significatly.